The effect of transfusion of blood products on ventricular assist device support outcomes. (14th October 2020) - Shore, Supriya; Hanff, Thomas C.; Mazurek, Jeremy A.; Seigerman, Matthew; Zhang, Robert; Grandin, Edward W.; Vorovich, Esther; Mather, Paul; Olt, Caroline; Howard, Jessica; Wald, Joyce; Acker, Michael A.; et al.
Abstract: Aims: Perioperative blood transfusions are common among patients undergoing left ventricular assist device (LVAD) implantation. The association between blood product transfusion at the time of LVAD implantation and mortality has not been described. Methods and results: This was a retrospective cohort study of all patients who underwent continuous flow LVAD implantation at a single, large, tertiary care, academic centre, from 2008 to 2014. We assessed used of packed red blood cells (pRBCs), platelets, and fresh frozen plasma (FFP). Outcomes of interest included all‐cause mortality and acute right ventricular (RV) failure. Standard regression techniques were used to examine the association between blood product exposure and outcomes of interest. A total of 170 patients were included in this study (mean age: 56.5 ± 15.5 years, 79.4% men). Over a median follow‐up period of 11.2 months, for every unit of pRBC transfused, the hazard for mortality increased by 4% [hazard ratio (HR) 1.04; 95% CI 1.02–1.07] and odds for acute RV failure increased by 10% (odds ratio 1.10; 95% CI 1.05–1.16). This association persisted for other blood products including platelets (HR for mortality per unit 1.20; 95% CI 1.08–1.32) and FFP (HR for mortality per unit 1.08; 95% CI 1.04–1.12). The most significant predictor of perioperative blood product exposure was a lower pre‐implant haemoglobin. Conclusions: Perioperative blood transfusions among patients undergoing LVAD implantation were associated with a higher risk for all‐cause mortality and acute RV failure. Of all blood products, FFP use was associated with worst outcomes. Future studies are needed to evaluate whether pre‐implant interventions, such as intravenous iron supplementation, will improve the outcomes of LVAD candidates by decreasing need for transfusions.